PAMABARIS PADA UPACARA ADAT PERKAWINAN MASYARAKAT DAYAK SIMPAKNG - Florensius, Florensius; Saman, Sisilya; Patriantoro, Patriantoro (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakÂ This study aims at (1) type of speech, (2) speech function, (3) values and norms in pama line speech at traditional wedding ceremony of Dyak Simpakng community. This research is a qualitative descriptive research using sociopragmatic approach, to understand socialization practices that are oriented in the context of indigenous marriage of Dayak Simpakng community. The data collection in this research is done by interview, obeservation and recording technique. After conducting a direct analysis of the pamabaris discourse on the traditional ceremony of the Dayak Simpakng community, it was found that: the type of my glorious utterance at the traditional wedding ceremony of the Dayak Simpakngmeliputi community: (1) the direct literal talk, 2) the direct speech is not literal; (3) indirect speech is not literal. The function of my glorious utterance in telling pama line at traditional marriage ceremony of Dayak Simpakng community include: (1) assertive, (2) directive, (3) expressive, (4) commissive, (5) declarative, both cultural values found in discourse pamabaris at traditional wedding ceremony of Dayak Simpkng communityÂ Keywords: Pama Line, Sosiopragmatik, Type and Function Of Speech, Value and NormÂ